2013
DOI: 10.3766/jaaa.24.2.4
|View full text |Cite
|
Sign up to set email alerts
|

The Contribution of a Frequency-Compression Hearing Aid to Contralateral Cochlear Implant Performance

Abstract: Frequency-lowering signal processing in hearing aids has re-emerged as an option to improve audibility of the high frequencies by expanding the input bandwidth.However, few studies have investigated the usefulness of the scheme as a bimodal option for cochlear implant users. In this study, that question was posed. It was hypothesized that, following fitting and a period of adjustment to a frequency-compression hearing aid, sound localization and speech perception would be improved compared to conventional ampl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
35
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(40 citation statements)
references
References 97 publications
(173 reference statements)
2
35
3
Order By: Relevance
“…These studies reported no benefit of FC for speech perception or sound localization either (Davidson et al, 2015;McDermott and Henshall, 2010;Park et al, 2012;Perreau et al, 2013). Perreau et al (2013) reported impaired vowel perception, in contrast to our results, even though we used FC across a much broader frequency range. This discrepancy most likely is a consequence of our signal-adaptive variant of FC, specifically aiming at preserving the vowels ( Figure 2B).…”
Section: Discussioncontrasting
confidence: 54%
See 2 more Smart Citations
“…These studies reported no benefit of FC for speech perception or sound localization either (Davidson et al, 2015;McDermott and Henshall, 2010;Park et al, 2012;Perreau et al, 2013). Perreau et al (2013) reported impaired vowel perception, in contrast to our results, even though we used FC across a much broader frequency range. This discrepancy most likely is a consequence of our signal-adaptive variant of FC, specifically aiming at preserving the vowels ( Figure 2B).…”
Section: Discussioncontrasting
confidence: 54%
“…So far, only a few studies have investigated FC in bimodal listeners, but no significant benefits were found. Yet, speech and consonant perception remained unaffected in those studies (Davidson et al, 2015;Hua et al, 2012;McDermott and Henshall, 2010;Park et al, 2012;Perreau et al, 2013). Perreau et al (2013) and Davidson et al (2015) investigated bimodal sound localization of daily sounds or words, but found no improvement as a result of FC in the HA.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Glista et al (2009) and Wolfe et al (2010;2011) found that consonant recognition was signifi cantly better when NLFC was enabled, although McDermott and Henshall (2010) and Perreau et al (2013) did not. A possible reason for the discrepancy in the results is that the studies that did not fi nd a benefi t from NLFC for consonant recognition both tested listeners with a hearing aid in one ear and although only fi ve subjects were tested and one subject showed a large improvement which accounted for most of the mean improvement.…”
Section: Aslmentioning
confidence: 93%
“…Several studies assessed the effect of NLFC on consonant recognition in quiet using closed set vowel-consonant-vowel (VCV) identifi cation tasks, either at a fi xed level (Glista et al, 2009;McDermott & Henshall, 2010;Perreau et al, 2013) or by using an cochlear implant in the contralateral ear. It is possible that NLFC is less benefi cial in this situation, as the listener may already have adequate access to high-frequency information from their cochlear implant.…”
mentioning
confidence: 99%